2016
DOI: 10.1002/ajmg.a.37862
|View full text |Cite
|
Sign up to set email alerts
|

FGFR‐associated craniosynostosis syndromes and gastrointestinal defects

Abstract: Craniosynostosis is a relatively common birth defect characterized by the premature fusion of one or more cranial sutures. Examples of craniosynostosis syndromes include Crouzon (CS), Pfeiffer (PS) and Apert (AS) syndrome, with clinical characteristics such as midface hypoplasia, hypertelorism and in some cases, limb defects. Mutations in Fibroblast Growth Factor Receptor-2 comprise the majority of known mutations in syndromic forms of craniosynostosis. A number of clinical reports of FGFR-associated craniosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…2 We present the clinical findings of a patient with SP diagnosed inutero due to a variant in FRFR2 gene. [8][9][10][11][12][13] Although most cases are diagnosed in their neonatal stage, prenatal diagnosis is possible. Three-dimensional obstetric ultrasound is the first-line diagnostic tool for suspected PS, being useful to verify suture closure in the third trimester of pregnancy for the most severe cases 14 although the diagnosis with lower gestational ages has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…2 We present the clinical findings of a patient with SP diagnosed inutero due to a variant in FRFR2 gene. [8][9][10][11][12][13] Although most cases are diagnosed in their neonatal stage, prenatal diagnosis is possible. Three-dimensional obstetric ultrasound is the first-line diagnostic tool for suspected PS, being useful to verify suture closure in the third trimester of pregnancy for the most severe cases 14 although the diagnosis with lower gestational ages has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical updates have been published on prevalence of tracheal cartilaginous sleeve [15] and progressive postnatal pansynostosis [16] in syndromic craniosynostosis, both of which highlight the particularly high burden of complications arising from FGFR2 mutations. Additional FGFR2 mutation-focused phenotype studies have been published on foramen magnum size [17], ophthalmic complications [18] and intestinal malrotation [19]. Complications were found to be differentially enriched in different syndromes: tracheal sleeve, proptosis and exposure keratitis were particularly associated with Pfeiffer syndrome, whereas insidious postnatal pansynostosis was most common in Crouzon syndrome.…”
Section: Syndromic Craniosynostosismentioning
confidence: 99%
“…A major group of human craniosynostosis syndromes, including Apert, Crouzon, or Pfeiffer syndromes, is caused by mutations leading to overactivation of Fgf receptors. Apert and Crouzon syndromes are caused by mutations in FGFR2 that increase affinity of the receptor for the ligand, and Pfeiffer syndrome is caused by mutations in either FGFR2 or FGFR1 ( Schell et al, 1995 ; Anderson et al, 1998 ; Hibberd et al, 2016 ). The search for specific ligands involved in the process of fusion of the sutures revealed that FGF10 can play a significant role in proper formation of skull shape.…”
Section: Role Of Fgf10 In Craniofacial Morphogenesismentioning
confidence: 99%